DIAZO TEST AS A SCREENING TEST OF TYPHOID FEVER A PRACTICAL APPROACH - J. Nugraha; Meiti Muljanti (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Typhoid fever represents an endemic acute infection with a high mortality, in this case a laboratory test is needed to establish theearly diagnosis. For this study the researchers prefer urine diazo test which is a relatively easy, simple and inexpensive test. The aimof this study is to know whether the urine diazo test can be used for screening typhoid fever and whether there is a concordance withthe Widal and TUBEX® TF serological tests. Forty patients aged 2–18 years, attending to the Jeremy Medical Service Clinic, Surabaya,suffering of fever more than 3 days were studied from June up to August 2010. Urine samples were tested by diazo test, while bloodsamples as comparison were tested by Widal and TUBEX® TF tests, and blood culture was carried out as the gold standard. The sensitivityand specificity of those tests were then recorded. From the 40 samples, 12 patients showed positive Salmonella typhi blood cultures,26 diazo positive, 22 Widal positive and 14 TUBEX® TF positive. Of the 12 positive blood cultures, 10 (83%) diazo positive, 7 (58%)Widal positive and 9 (75%) TUBEX® TF positive were found. The sensitivity and specificity of diazo test was 83% and 43%, Widal test58% and 46%, TUBEX® TF test 75% and 82%. It is shown that the Diazo test had a higher sensitivity value, while the TUBEX® TF testshowed a higher level of specificity. In conclusion, so far it can be concluded that the Diazo test is quite reliable in aiding the diagnosisof typhoid fever and can be considered as a screening test for typhoid fever.